Fuzzy Gain Scheduling PID Control for Position of the AR.Drone - Agung Prayitno; Veronica Indrawati; Ivan Immanuel Trusulaw (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper describes the design and implementation of fuzzy gain scheduling PID control for position of the AR.Drone. This control scheme uses 3 PID controllers as the main controller of the AR.Drone, in this case to control pitch, roll and throttle. The process of tuning parameters for each PID is done automatically by scheduling determined by Takagi-Sugeno-Kang (TSK) fuzzy logic model. This paper uses five function sets of PID parameters that will be evaluated by fuzzy logic in order to tune PID controllers. Error position (x,y,z), as inputs of controller, enters the PID Signal block yielding the ouputs in term of error, integral error and differential error. These signal become the inputs of the fuzzy scheduler to yield outputs pitch, roll and throttle to the AR.drone. The control scheme is implemented on the AR.Drone to make it fly to forming a square in the room. The experimental results show that the control scheme can follow the desired points, and process scheduling PID parameters can be shown.